Application of Dance Movement Therapy to Life-Death Education of College Students Under Educational Psychology - Yang, Liu; Li, Fen (Frontiers in Psychology, 2022)
The present work aims to efficiently carry out life-death education (LDE) for college students, improve their psychological problems, and reduce suicide accidents by combining LDE with Dance Movement Therapy (DMT). DMT is a psychosomatic cross therapy that treats mental or physical diseases through dance or improvisation. Firstly, this paper introduces LDE and DMT and designs the activities of DMT intervention. Secondly, the relationship between DMT and LDE is analyzed. Finally, a questionnaire survey is conducted on the research objects. The research objects are divided into the experimental group receiving DMT intervention, the control group participating in sports dance courses, and the benchmark group. The research data show no significant difference in interpersonal skills and emotional psychology among the three groups. The DMT intervention group has substantial changes in other factors except for the conflict control ability before and after the intervention. In addition, the questionnaire survey results after the intervention demonstrate that the DMT intervention group gets a significantly higher score in the interpersonal relationship, interpersonal relationship building ability, moderate rejection ability, self-disclosure ability, and emotional support ability. Therefore, DMT intervention positively impacts college students’ interpersonal relationships. After the sports dance course, there are differences in the total score of interpersonal ties and scores of interpersonal relationships building ability, self-disclosure ability, and emotional support ability in the control group, but with no significant difference in moderate rejection ability and conflict control ability. Therefore, compared with traditional psychotherapy methods, the DMT method reported here is conducive to releasing pressure and alleviating physical and mental anxiety. The research content provides new ideas for psychological education in colleges and universities and contributes to improving college students’ suicidal tendencies and helping college students grow up healthily.